Identification of independent association signals and putative functional variants for breast cancer risk through fine-scale mapping of the 12p11 locus. Issue 1 (December 2016) - Zeng, Chenjie; Guo, Xingyi; Long, Jirong; Kuchenbaecker, Karoline; Droit, Arnaud; Michailidou, Kyriaki; Ghoussaini, Maya; Kar, Siddhartha; Freeman, Adam; Hopper, John; Milne, Roger; Bolla, Manjeet; et al.
Abstract Background Multiple recent genome-wide association studies (GWAS) have identified a single nucleotide polymorphism (SNP), rs10771399, at 12p11 that is associated with breast cancer risk. Method We performed a fine-scale mapping study of a 700 kb region including 441 genotyped and more than 1300 imputed genetic variants in 48, 155 cases and 43, 612 controls of European descent, 6269 cases and 6624 controls of East Asian descent and 1116 cases and 932 controls of African descent in the Breast Cancer Association Consortium (BCAC;http://bcac.ccge.medschl.cam.ac.uk/ ), and in 15, 252BRCA1 mutation carriers in the Consortium of Investigators of Modifiers ofBRCA1/2 (CIMBA). Stepwise regression analyses were performed to identify independent association signals. Data from the Encyclopedia of DNA Elements project (ENCODE) and the Cancer Genome Atlas (TCGA) were used for functional annotation. Results Analysis of data from European descendants found evidence for four independent association signals at 12p11, represented by rs7297051 (odds ratio (OR) = 1.09, 95 % confidence interval (CI) = 1.06–1.12;P  = 3 × 10-9 ), rs805510 (OR = 1.08, 95 % CI = 1.04–1.12, P  = 2 × 10-5 ), and rs1871152 (OR = 1.04, 95 % CI = 1.02–1.06;P  = 2 × 10-4 ) identified in the general populations, and rs113824616 (P  = 7 × 10-5 ) identified in the meta-analysis of BCAC ER-negative cases andBRCA1 mutation carriers. SNPs rs7297051, rs805510 and rs113824616 were also associated with breast cancer risk atP  < 0.05 in East Asians, but none of the associations were statistically significant in African descendants. Multiple candidate functional variants are located in putative enhancer sequences. Chromatin interaction data suggested thatPTHLH was the likely target gene of these enhancers. Of the six variants with the strongest evidence of potential functionality, rs11049453 was statistically significantly associated with the expression ofPTHLH and its nearby geneCCDC91 atP  < 0.05. Conclusion This study identified four independent association signals at 12p11 and revealed potentially functional variants, providing additional insights into the underlying biological mechanism(s) for the association observed between variants at 12p11 and breast cancer risk.